Child Care and the Employment Behavior of Single and Married Mothers - Jean Kimmel (W.E. Upjohn Institute for Employment Research, 1992)
This paper examines the relationship between the cost of child care and the employment behavior of married and single mothers. The data used in this paper are from the 1987 SIPP, the first SIPP panel to utilize an improved probing of child care usage and expenditures. A primary contribution of this paper stems from the use of these improved child care data. A second contribution is to provide a clear comparison between single mothers and married mothers. A third contribution of this paper is its detailed discussion of participation elasticities, with a comparison of elasticities derived from different measures of the price of child care. This permits a meaningful comparison between the different child care price elasticities reported by different child care researchers in recent years. The paper's primary estimating equations examine the impact of changes in the market wage and the hourly price of child care on employment and hours of paid child care. The most fundamental result described in this paper is that increases in the market wage significantly increase the probability of labor force participation for married and single mothers, while increases in the price of care reduce the probability of labor force participation.
Keywords: J2; I3; 330; child; care; employment; mothers; Kimmel